2015
DOI: 10.1177/1358863x15574321
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-converting enzyme inhibitor or angiotensin receptor blocker use is associated with reduced major adverse cardiovascular events among patients with critical limb ischemia

Abstract: Angiotensin converting enzyme inhibitors (ACEIs) or angiotensin receptor blockers (ARBs) are recommended for secondary prevention in peripheral artery disease, but their effectiveness in patients with critical limb ischemia (CLI) is uncertain. We reviewed 464 patients with CLI who underwent diagnostic angiography or endovascular intervention from 2006-2013 at a multidisciplinary vascular center. ACEI or ARB use was assessed at the time of angiography. Major adverse cardiovascular events (MACE), mortality, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(37 citation statements)
references
References 59 publications
0
35
1
1
Order By: Relevance
“…Identifying high-risk patients and optimizing medical management of co-morbidities is critical to improving outcomes in this challenging patient population. [18][19][20][21]…”
Section: Introductionmentioning
confidence: 99%
“…Identifying high-risk patients and optimizing medical management of co-morbidities is critical to improving outcomes in this challenging patient population. [18][19][20][21]…”
Section: Introductionmentioning
confidence: 99%
“…In particular, ramipril has been shown to retard atherosclerotic progression in the carotid arteries and to reduce a composite endpoint of MI, stroke or cardiovascular death in patients with vascular disease 38. Further, the use of an ACE inhibitor or angiotensin receptor blocker in patients with CLI has been associated with significant reductions in MACE and mortality 39. Based on this, current consensus guidelines include a IIa recommendation supporting the use of ACE inhibitors in patients with symptomatic PAD regardless of blood pressure 11…”
Section: Treatmentmentioning
confidence: 99%
“…However, there are no randomized clinical trials in patients with CLI that have shown a decrease in revascularization rate, an increase in patency, a lower amputation rate, or faster wound healing with medical therapy alone. 21 A number of observational and single center studies have shown that patients with PAD and CLI are under-treated with guideline-recommended therapies (anti-platelet therapy, statins, and antihypertensive therapies). 22 Furthermore, under-treatment with guideline-recommended therapies was associated with increased repeat revascularization and amputation in patients undergoing revascularization.…”
Section: Critical Limb Ischemiamentioning
confidence: 99%